Identifikasi beban kerja mental operator forklift PT. NDIS menggunakan metode NASA-Task Load Index - Yusuf, Rusli; Fais, Moh Ainul; Chusaini, Achmad (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to evaluate the mental workload of forklift operators at PT. NDIS, using the NASA-Task Load Index (NASA-TLX) method. Data was collected through an online questionnaire, with results indicating a